Germany and the European East in the Twentieth Century. - Mühle, Eduard (German historical perspectives., 2003)
How did German society perceive the European East during the short twentieth century? What were the mental maps Germans constructed as their images of the European East? How did these images alter over time due to changing political systems and to what extent did those mental perceptions influence political action and the relationship between Germany and Eastern Europe? Tackling questions such as these, this book looks at the complicated relationship between Germany and the European East. Politically significant, this relationship was often fraught with tension, always delicate and never easy.